Tocilizumab for juvenile idiopathic arthritis: a single-center case series - Yazılıtaş, Fatma (2019)
BACKGROUND: Juvenile idiopathic arthritis (JIA) is the commonest chronic rheumatic disease among children. When not treated effectively, JIA can lead to functional disability, due to joint damage, along with long-term morbidities. OBJECTIVES: To describe the use of tocilizumab therapy for 11 patients with polyarticular JIA (pJIA) and sys-temic JIA (sJIA) who presented inadequate response or were refractory to disease-modifying anti-rheumatic drugs (DMARDs) and/or other biological therapies; and to evaluate its benefits, safety and tolerability. DESIGN AND SETTING: Observational retrospective case series at a tertiary-level training and research hospital. METHODS: We reviewed the medical records of 11 consecutive patients with JIA who received tocilizum-ab (anti-IL-6) therapy in our pediatric nephrology and rheumatology outpatient clinic. We analyzed their demographic data, clinical and laboratory findings, treatment response and adverse reactions. We deter-mined the efficacy of tocilizumab treatment using the American College of Rheumatology (ACR) pediatric (Pedi) response criteria, including ACR Pedi 30, 50, 70 and 90 scores. We used the Wilcoxon test to compare measurements before and after treatment. RESULTS: Tocilizumab was given to seven patients with sJIA and four with pJIA (one of the pJIA patients was rheumatoid factor-positive). In most patients, we observed improvement of symptoms, absence of ar-ticular and extra-articular inflammation and continued inactive disease. ACR Pedi 30, 50 and 70 scores were achieved by 90.9% of the patients. Five patients showed minor side effects, possibly due to use of tocilizumab. CONCLUSIONS: Tocilizumab therapy should be considered for treating patients with diagnoses of pJIA or sJIA who are resistant to non-biological DMARDs and/or other biological therapies.